Nonenzymatic sensor based on polythiophene/titanium dioxide (PTh/TiO2) composite for the determination of malathion in water - Gursoy, Songül Şen; Kahraman, Derya (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study presents a novel nonenzymatic pesticide sensor utilizing a polythiophene/TiO2 (PTh/TiO2 ) film deposited on a glassy carbon (GC) electrode as the working electrode. The thiophene monomer was polymerized onto TiO2 by cyclic voltammetric method in the range of 0.0-2.5 V with 15 cycles at room temperature. The prepared electrode was used for the sensitive and selective detection of malathion thus providing the basis for facile electrochemical quantification. The surface morphology and crystal structure of the (PTh/TiO2 ) film were studied by SEM and XRD. FTIR was used for the structural analysis of (PTh/TiO2 ) film. FTIR results indicated that the PTh/TiO2 composite structure was formed. The smooth surface morphology of PTh/TiO2 was supported by SEM results. XRD analysis verified that PTh is covered on TiO2 particles. The crystal phase of TiO2 was changed to amorph state after PTh modification. Additionally, the electrochemical characterization of polymer film and its response to malathion was examined by the CV method. Under optimized operational conditions, the response of the pesticide sensor was measured by CV in the range of -1 to 2.3 V versus the Ag/AgCl reference electrode due to the electrooxidation of malathion. The analysis focused on current values at -0.73 V, where the reduction of the PTh/TiO2 system occurred upon the addition of known amounts of malathion. The PTh/TiO2 composite film was sensitive to malathion in a linear range from 9.9 ppm to 436 ppm. The sensitivity was calculated as 57.5 μA/ µM cm2 whereas the detection limit was calculated as 7.45 µM. The maximum reaction rate was estimated as 767 μA. The developed sensor also showed good selectivity and reproducibility. The nonenzymatic pesticide sensor was successfully applied to detect malathion in tap water with at least 90% recovery.